2016
DOI: 10.1063/1.4943058
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale micromagnetic simulation of Nd-Fe-B sintered magnets with Dy-rich shell structures

Abstract: Large-scale micromagnetic simulations have been performed using the energy minimization method on a model with structural features similar to those of Dy grain boundary diffusion (GBD)-processed sintered magnets. Coercivity increases as a linear function of the anisotropy field of the Dy-rich shell, which is independent of Dy composition in the core as long as the shell thickness is greater than about 15 nm. This result shows that the Dy contained in the initial sintered magnets prior to the GBD process is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Micromagnetic models which are used for the analysis and design of permanent magnets are huge. Typically the number of finite elements exceeds 20 million elements [41,32]. As a consequence fast solvers for computing the demagnetization curve are required.…”
Section: Introductionmentioning
confidence: 99%
“…Micromagnetic models which are used for the analysis and design of permanent magnets are huge. Typically the number of finite elements exceeds 20 million elements [41,32]. As a consequence fast solvers for computing the demagnetization curve are required.…”
Section: Introductionmentioning
confidence: 99%
“…The grains with higher anisotropy field have a composition (Nd 1−x Dy x ) 2 Fe 14 B. Following Oikawa et al [44] we decrease the spontaneous magnetization M s linearly with increasing Dy-content. For the grains with higher anisotropy field we used (Nd 0.9 Dy 0.1 ) 2 Fe 14 B or (Nd 0.66 Dy 0.34 ) 2 Fe 14 B with a magnetization μ 0 M s =1.52 T and 1.3T, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…This indicates that the over-high concentration of HRE in the HRE-rich shells is unnecessary but causes an unexpected waste of HRE resources. In addition, a large-scale micromagnetic simulation by Oikawa et al 38 revealed that a 15 nm-thick Dy-rich shell is sufficient for coercivity enhancement. Therefore, for highly efficient use of the HRE sources, a deep diffusion depth of HRE and thin HRE-rich shell should be achieved by GBD.…”
Section: Resultsmentioning
confidence: 99%